Relative density influence on the liquefaction potential of sand with fines - Bensoula, Mohamed; Bousmaha, Mohammed; Missoum, Hanifi (Revista de la Construcción. Journal of Construction, 2022)
Liquefaction is a loss in soil’s resistance which can lead to disastrous and expensive consequences in terms of human lives and material damages, hence the interest of this laboratory study. The article explores the relative density influence in addition to the main parameter of the fines content on the liquefaction potential of soils. The study is based on a very large number of undrained monotonic triaxial tests undertaken on samples of reconstituted saturated sand and silt mixtures with 6 levels of initial relative density ranging from 15 to 90%. The materials used are levied from different level of deepness in the coastal region of Kharouba in the wilaya of Mostaganem. In this experiment, the sand-silt mixtures were separated to form the study samples. The aim of this work is, on one hand, to confirm and update the results of previous works (Bensoula et al., 2018) and on the other hand the study of the influence of relative density on the liquefaction potential of soils and the introduction of the concept of relative density threshold. The results of the tests confirm that the studied soil is most likely to be liquefied at a fines content between 0 and 30% depending on the equivalent intergranular voids and the equivalent relative density. These parameters are primordial for the characterization of soils sensitivity to liquefaction. In this study, the results showed that the resistance to liquefaction increases in a linear way with the relative density up to a threshold relative density value according to the fines content, which means that increasing the relative density improves the liquefaction resistance but only up to a threshold value of relative density given according to fines content.